2020
DOI: 10.1080/15568318.2020.1861394
|View full text |Cite
|
Sign up to set email alerts
|

Electric carsharing and micromobility: A literature review on their usage pattern, demand, and potential impacts

Abstract: Shared e-mobility is a category of emerging mobility services that includes electric carsharing, e-bike sharing, and e-scooter sharing. These services are expected to reduce the negative externalities of road transport in cities, which is currently dominated by fossil-fuel-powered private car trips. In order to better inform the development and promotion of these services and indicate directions for further research, we conducted a comprehensive review of existing literature on the three shared e-mobility mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(38 citation statements)
references
References 50 publications
2
33
0
3
Order By: Relevance
“…Because the EVCARD relies on mobile apps and the elderly people have difficulties using a smart phone [28], it is not surprising to find out that a large proportion of members were young. e mean age of the studied members was about 34.1. is finding is consistent with the previous research, which found that the age of the majority of electric carsharing users was between 30 to 40 [12].…”
Section: General Situationsupporting
confidence: 93%
See 3 more Smart Citations
“…Because the EVCARD relies on mobile apps and the elderly people have difficulties using a smart phone [28], it is not surprising to find out that a large proportion of members were young. e mean age of the studied members was about 34.1. is finding is consistent with the previous research, which found that the age of the majority of electric carsharing users was between 30 to 40 [12].…”
Section: General Situationsupporting
confidence: 93%
“…However, as the price of the private car became much cheaper, carsharing turned to be less attractive until the rising fuel prices and heavy road congestion have drawn the public's attention back to carsharing [8]. In recent years, shared mobility becomes a hot topic in transport development, and so does electrification [12,16,17]. Electric carsharing, a form of carsharing which rents EVs to people, combines these two items and is expected to inherit their positive impacts on sustainable transport development, including guiding the public to form a sustainable travel behavior [6], improving the accessibility and flexibility of the urban transport [12], reducing car ownership [5], vehicle kilometres of travel [9], traffic congestion [18], parking land use [18], and greenhouse gas emissions [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They reviewed data sources, system characteristics, users, and impacts. Liao and Correia reviewed four themes for e-scooter use, i.e., performance, descriptions of the available systems, demand estimation studies, and impact evaluation studies [29]. They concluded that high-income and educated middle-aged men were more likely to be e-scooter users.…”
Section: Introductionmentioning
confidence: 99%